2022
DOI: 10.1103/physrevb.106.014515
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of superconducting states to the impurity location in layered materials

Abstract: The family of multilayered superconductors derived from doped topological insulators in the family of Bi 2 Se 3 has been found to be unusually robust against nonmagnetic disorder. Recent experimental studies have highlighted the fact that the location of impurities could play a critical role in this puzzling robustness. Here we investigate the effects of four different types of impurities, on-site, interstitial, intercalated, and polar, on the superconducting critical temperature. We find that different compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The gap is measured in units of the topological gap for the topological pristine system T . In particular, it is observed that the location of the impurity strongly impacts the gap of the system [90]. The resulting gap of the defective system can range from the pristine value, observed for impurities at the exchange maximum, to nearly zero, observed for impurities away from the exchange maximum [Fig.…”
Section: Strong Impurities In Topological Moiré Superconductorsmentioning
confidence: 99%
“…The gap is measured in units of the topological gap for the topological pristine system T . In particular, it is observed that the location of the impurity strongly impacts the gap of the system [90]. The resulting gap of the defective system can range from the pristine value, observed for impurities at the exchange maximum, to nearly zero, observed for impurities away from the exchange maximum [Fig.…”
Section: Strong Impurities In Topological Moiré Superconductorsmentioning
confidence: 99%
“…In this class of materials, despite the threefold rotational symmetry of the lattice, bulk superconducting (SC) properties consistently show peculiar twofold symmetry [3][4][5][6][7][8][9] that points to the realization of an odd-parity gap function with E u symmetry. Although this gap function is unconventional and strongly anisotropic, the superconductivity is nonetheless protected from disorder due to the generalized Anderson's theorem, thanks to the additional orbital degrees of freedom and layered structure [10][11][12].…”
Section: Introductionmentioning
confidence: 99%